Barriers felt by nurses related to childhood basic immunisation in East Nusa Tenggara: A phenomenological study - Petrus Kanisius Siga Tage; Herliana Monika Azi Djogo (JKP (Jurnal Keperawatan Padjajaran), 2022)
Background: Immunisation barriers can increase morbidity and mortality associated with vaccine-preventable diseases. Understanding barriers to childhood vaccination is critical to informing effective interventions to maximise coverage.